SIMULASI DAN ANALISIS SISTEM TATA KELOLA AIR DI LAHAN PASANG SURUT: STUDI AWAL PADA PERKEBUNAN KELAPA SAWIT DI KALIMANTAN SELATAN - Henny Lydiasari; Winarna Winarna (Jurnal Penelitian Kelapa Sawit, 2019)
Oil palm plantations on tidal swamp land are increasing with the potential of land reach 20.1 million hectares due to unavailable mineral land which can be used. The limitation of optimal land for oil palm in Indonesia is currently a factor that encourages the use of sub-optimal land, one of which is tidal land. The use of tidal land has certain constraints such as soil acidity, low soil fertility, poor soil drainage conditions, lack of water and increased pyrite oxidation during dry periods which have a negative impact on oil palm growth and productivity. This preliminary study examines the effects of existing water governance to get the right solution and can be applied in the future. Modeling on HEC-RAS 4.1 software produces a simulation of the physical phenomena of channels in the land. The overall results show that the condition of the water governance system in the observation block is not optimal so that the inundated areas range from 65% due to the lack of good water management systems such as the drainage of the canals, the lack of water buildings and even the sluices so that in an uncontrolled area. This obstacle can be overcome by improving water management, such as canal washing, construction of water buildings, including culverts, bridges, crop harvesting, stoplogs and sluice gates. Water management system plays an important role in controlling water in the garden area so that in the rainy season, water can be channeled to outlets and in the dry season, water can survive in the garden area.This study is expected to be a reference in improving the water management system in that location.